Analysis of Gaseous and Gaseous-Dusty, Premixed Flame Propagation in Obstructed Passages with Tightly Placed Obstacles - Furkan Kodakoglu; Sinan Demir; Damir Valiev; V’yacheslav Akkerman (Fluids, 2020)
A recent predictive scenario of premixed flame propagation in unobstructed passages is extended to account for obstructions that can be encountered in facilities dealing with explosive materials such as in coalmines. Specifically, the theory of globally-spherical, self-accelerating premixed expanding flames and that of flame acceleration in obstructed conduits are combined to form a new analytical formulation. The coalmining configuration is imitated by two-dimensional and cylindrical passages of high aspect ratio, with a comb-shaped array of tightly placed obstacles attached to the walls. It is assumed that the spacing between the obstacles is much less or, at least, does not exceed the obstacle height. The passage has one extreme open end such that a flame is ignited at a closed end and propagates to an exit. The key stages of the flame evolution such as the velocity of the flame front and the run-up distance are scrutinized for variety of the flame and mining parameters. Starting with gaseous methane-air and propane-air flames, the analysis is subsequently extended to gaseous-dusty environments. Specifically, the coal (combustible, i.e., facilitating the fire) and inert (such as sand, moderating the process) dust and their combinations are considered, and the impact of the size and concentration of the dust particles on flame acceleration is quantified. Overall, the influence of both the obstacles and the combustion instability on the fire scenario is substantial, and it gets stronger with the blockage ratio.